2021
DOI: 10.1038/s41420-021-00501-4
|View full text |Cite
|
Sign up to set email alerts
|

Smoothened inhibition leads to decreased cell proliferation and suppressed tissue fibrosis in the development of benign prostatic hyperplasia

Abstract: Benign prostatic hyperplasia (BPH) is a common disease in aging males. It has been proven that the Hedgehog (HH) is implied as an effective and fundamental regulatory growth factor signal for organogenesis, homeostasis, and regeneration. Smoothened (SMO), as the major control point of HH signals, activates aberrantly in most human solid tumors. However, the specific function of SMO and its downstream glioma-associated oncogene (GLI) family in BPH has not been well understood. Here, we first revealed that the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Cordon-Cardo et al firstly reported that p27KIP1, a negative regulator of the cell cycle, decreased within hyperplastic prostate tissues, while lack of the p27KIP1 gene increased the proliferative activity of prostatic cells [24]. Our recently published evidence also suggested that bone morphogenetic protein 5 (BMP5) and Smoothened (SMO), alongside the downstream glioma-associated oncogene (GLI) family, stimulated cellular proliferation of BPH-1 and WPMY-1 cells by promoting cell cycle progression [25,26]. Apoptosis has been known as one of the programmed cell death mechanisms.…”
Section: Overview Of Benign Prostate Hyperplasiamentioning
confidence: 89%
“…Cordon-Cardo et al firstly reported that p27KIP1, a negative regulator of the cell cycle, decreased within hyperplastic prostate tissues, while lack of the p27KIP1 gene increased the proliferative activity of prostatic cells [24]. Our recently published evidence also suggested that bone morphogenetic protein 5 (BMP5) and Smoothened (SMO), alongside the downstream glioma-associated oncogene (GLI) family, stimulated cellular proliferation of BPH-1 and WPMY-1 cells by promoting cell cycle progression [25,26]. Apoptosis has been known as one of the programmed cell death mechanisms.…”
Section: Overview Of Benign Prostate Hyperplasiamentioning
confidence: 89%
“…The disruption of the molecular mechanisms in these two processes may lead to BPH [ 48 ]. Although the mechanism of BPH is not fully understood, previous studies reported that inducing apoptosis and the inhibition of cell proliferation contributes to the treatment of BPH [ 49 , 50 ]. A decrease in apoptotic activity plays an important role in the BPH pathogenesis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell lines obtained and cultured, CCK-8 assay, total RNA extraction, RNA reverse transcription, qRT-PCR analysis, Western blot analysis, hematoxylin and eosin (H&E) staining and masson’s trichrome staining analysis were performed as we previously described [ 35 , 36 ]. Primer sequences were summarized in Additional file 1 : Table S1.…”
Section: Methodsmentioning
confidence: 99%